MEASUREMENT AND ANALYSIS OF TEACHERS’ PROFESSIONAL PERFORMANCE - Leus, Olga; Maslak, Anatoly (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The relevance of the measurement and analysis of teachers’ professional performance is based on the fact that teachers largely determine the quality of education at schools. The measurement of the latent variable "teacher’s professional performance" is done within the framework of the theory of latent variables based on the Rasch model. It was shown that the set of indicators has a high differentiating ability. The results of the measurement of this latent variable are used to compare the quality of professional activities of teachers of mathematics, history, Russian language, and literature as well as primary school teachers. No statistically significant differences were found between the professional performance of teachers of mathematics, history, and primary school teachers. The quality of professional activity of teachers of Russian language and literature is lower. The results of the measurement of teachers’ professional performance were used for comparison of schools. As one would expect, the highest quality of professional performance of teachers is in high schools and lowest in the primary schools; secondary schools occupy an intermediate position. Teachers’ professional performance is defined operationally, using a set of indicators. This set of indicators can be adjusted to clarify the content of the latent variable "teacher’s professional performance".